The Use of Buzzers by Political Parties Which Result in Black Campaign Practices in Indonesia - Umami, Allan Mustafa; Al Qindy, Fatria Hikmatiar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Buzzers are known as an effective marketing tool to sell a product. With the development of information technology, the use of buzzers is no longer limited to marketing products. Buzzers in Indonesia are now also used as a campaign tool by political parties. Unfortunately, many political parties' use of buzzers on social media is indicated as leading to black campaigns. The Black Campaign is a campaign to vilify political opponents whose truth cannot be justified. Political parties have a very important role in Indonesia, namely as a means or participant in elections, whether for the Presidential election, central or regional People's Representative Council, regional head elections. Political parties that are given status as election participants must continue to carry out their activities by prioritizing the spirit of Indonesian unity. Political parties do not just gather sympathizers or cadres for the sole purpose of power. Political Parties must be responsible for producing leaders and sympathizers who have character and act in the interests of the nation and state, in particular maintaining the unity of Indonesia by continuing to maintain brotherhood between tribes, religions and sects in Indonesia. Political parties are prohibited from carrying out black campaigns because black campaigns can cause social tension due to the spread of unfounded information and lead to forming hatred towards political opponents. The formulation of the research problem is: How does the law on the use of buzzers by political parties result in the practice of black campaigns in Indonesia? The purpose of this research is to find out how the law on the use of buzzers by political parties has resulted in the practice of black campaigns in Indonesia. The research method used is normative research. This research is based on primary and secondary research. Primary research is research that is based on statutory regulations, while secondary research is based on theories from experts sourced from books and journals. The results of this research are that political parties have an important role in maintaining unity in Indonesia and must use campaign tools in accordance with statutory regulations.